High-Yield Production of Catalytically Active Regulatory [NiFe]-Hydrogenase From Cupriavidus necator in Escherichia coli - Fan, Qin; Caserta, Giorgio; Lorent, Christian; Zebger, Ingo; Neubauer, Peter; Lenz, Oliver; Gimpel, Matthias (Frontiers in Microbiology, 2022)
Hydrogenases are biotechnologically relevant metalloenzymes that catalyze the reversible conversion of molecular hydrogen into protons and electrons. The O2-tolerant [NiFe]-hydrogenases from Cupriavidus necator (formerly Ralstonia eutropha) are of particular interest as they maintain catalysis even in the presence of molecular oxygen. However, to meet the demands of biotechnological applications and scientific research, a heterologous production strategy is required to overcome the low production yields in their native host. We have previously used the regulatory hydrogenase (RH) from C. necator as a model for the development of such a heterologous hydrogenase production process in E. coli. Although high protein yields were obtained, the purified enzyme was inactive due to the lack of the catalytic center, which contains an inorganic nickel-iron cofactor. In the present study, we significantly improved the production process to obtain catalytically active RH. We optimized important factors such as O2 content, metal availability, production temperature and time as well as the co-expression of RH-specific maturase genes. The RH was successfully matured during aerobic cultivation of E. coli by co-production of seven hydrogenase-specific maturases and a nickel permease, which was confirmed by activity measurements and spectroscopic investigations of the purified enzyme. The improved production conditions resulted in a high yield of about 80 mg L–1 of catalytically active RH and an up to 160-fold space-time yield in E. coli compared to that in the native host C. necator [<0.1 U (L d) –1]. Our strategy has important implications for the use of E. coli K-12 and B strains in the recombinant production of complex metalloenzymes, and provides a blueprint for the production of catalytically active [NiFe]-hydrogenases in biotechnologically relevant quantities.